A field investigation of flight anxiety: Evidence of gender differences in consumer behaviors among Las Vegas passengers - Lindsey A Harvell; Tyler Stillman; Gwendelyn S Nisbett; Kyle Cranney; Amber Schow (Journal of Airline and Airport Management, 2016)
Purpose: This study examines how anxious the Las Vegas public is through a case study of one local international airport.